EFEKTIFITAS SENAM HAMIL TERHADAP NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI BPM A. H KOTA DEPOK TAHUN 2024 - Azis, Aninditya (Journal of Midwifery Tiara Bunda, 2024)
Background: During the third trimester of pregnancy, the mother will experience weight gain, hormonal influences, and others. As an effort to adjust to the excessive weight of the body, the spine pushes back and causes the mother to feel aches in the back, varicose veins, and cramps in the legs. One of the treatments in the third trimester is exercise, one of which is pregnancy exercise. Objective: This study aims to determine the relationship between pregnancy exercise and back pain in third trimester pregnant women at BPM A. H, Depok City. Methodology: This type of research is quantitative analysis. The location of the research was carried out at BPM A. H, Depok City, in the period June 2022–July 2022. The sample in this study was the third-trimester pregnant women at BPM A. H Depok City, as many as 20 people. The data used in this study is primary data obtained from the results of the questionnaire. Results: Value calculated = 0.000, which is less than 0.05. This indicates that at BPM A.H Depok City in 2022, there is a significant correlation between pregnant exercise and back pain. According to the data, the average pain level prior to pregnancy exercise was 4.9%, while the average pain level after pregnancy exercise was 1.8%. Conclusion: The conclusion of this study is that pregnancy exercise can reduce back pain. Suggestion: The influence of pregnancy exercise on back pain in third trimester pregnant women can make pregnancy exercise a recommended sport.